2021
DOI: 10.1002/solr.202000764
|View full text |Cite
|
Sign up to set email alerts
|

Functional ZnO/TiO2 Bilayer as Electron Transport Material for Solution‐Processed Sb2S3 Solar Cells

Abstract: Electron transport materials (ETMs) are considered a keystone component of third‐generation solar cells. Among the alternative ETM, metal oxide bilayers have attracted increasing attention due to their easy processing and tunability of cascade energy alignment. Herein, a metal oxide bilayer that combines ZnO and TiO2 compact films (ZnO/TiO2) is implemented as ETM for solution‐processed Sb2S3 planar solar cells. The bilayer ETM achieves the highest photovoltaic performance when compared with devices based on si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 39 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Briefly, each SPV transient is composed of a fast initial decay associated with the bandto-band charge recombination, followed by a nearly exponential decay related to the surface/interface recombination in the multilayer systems. 41 By fitting the SPV data using a bi-exponential model, it is observed that the recombination time (τ) decreases as the number of layers increases, i.e., τ FPF = 103.65 ms, τ FPFP = 90.57 ms and τ FPFPF = 67.75 ms. On the other hand, F and P single layer exhibited τ of 710 and 44.7 ms, respectively. In inorganic materials, larger recombination times are associated to a larger density of interfacial trap states.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, each SPV transient is composed of a fast initial decay associated with the bandto-band charge recombination, followed by a nearly exponential decay related to the surface/interface recombination in the multilayer systems. 41 By fitting the SPV data using a bi-exponential model, it is observed that the recombination time (τ) decreases as the number of layers increases, i.e., τ FPF = 103.65 ms, τ FPFP = 90.57 ms and τ FPFPF = 67.75 ms. On the other hand, F and P single layer exhibited τ of 710 and 44.7 ms, respectively. In inorganic materials, larger recombination times are associated to a larger density of interfacial trap states.…”
Section: Resultsmentioning
confidence: 99%
“…These are demonstrated by the notable increase of publication numbers for "Sb 2 S 3 films" and "Sb 2 S 3 solar cells" related research articles in the past decade (Figure 3a), which resulted in its 𝜂 from an initial efficiency of 2.0% in 1992 to a champion efficiency of 7.50-8.32% in recent years (Figure 3b). [31][32][33]56] Presently, the Sb 2 S 3 films can be prepared by chemical bath deposition (CBD), [31,32,[57][58][59] in situ hydrothermal method, [60][61][62][63][64][65][66][67] spin coating, [28,34,38,[68][69][70][71][72][73][74][75][76] atomic-layer deposition (ALD), [77][78][79][80] rapid thermal evaporation (RTE), [81][82][83][84] spray pyrolysis, [85] and sputtering. [86] Solution-processed methods (i.e., CBD, spin coating, hydrothermal) have low cost and no rigescent equipment requirement.…”
Section: Sb 2 S 3 Film Engineering and Photovoltaic Devicesmentioning
confidence: 99%
“…[8] Unfortunately, the inert nature of TiO 2 film leads to the absence of transition layer at TiO 2 / Sb 2 Se 3 interface, and the insufficient optimization of conduction band alignment toward heterojunction interface may hinder the carriers transport across the pn junction. [26] The approaches like Zn, Li doping in TiO 2 , [27][28] ZnO/TiO 2 double ETL [29] proven effective to mitigate the conduction band offset of TiO 2 /Sb 2 S 3 interface, which should be carried on TiO 2 /Sb 2 Se 3 interface as well. Hence, new interface modification strategies and/or composited ETL should be tapped to optimize bandgap alignment and interface quality of ITO/TiO 2 /Sb 2 Se 3 , by which the obstacles on the developing process of VTD-processed Cd-free Sb 2 Se 3 TFSC could be removed.…”
Section: An Undesirable P-n Heterojunction Interface Ofmentioning
confidence: 99%